Odpowiedź:
Zd 1.
a) [tex]\frac{12x^{2} }{12}[/tex] = 12
d) [tex]\frac{-3^{3} }{9}[/tex] = [tex]\frac{-27}{9}[/tex] = -3
Zd 2.
a) [tex]5^{9} * 5^{8} = 5^{9+8} = 5^{17}[/tex]
b) [tex]9^{9} * 9 * 9^{9} = 9^{9+1+9}=9^{19}[/tex]
Zd 3.
a) [tex](4x)^{3} = 64x^{3}[/tex]
d)[tex](\frac{-5x^{7} }{2y}) ^{3} =- \frac{(5x^{7} )^{3} }{(2y)^{3} } = - \frac{125x^{21} }{8y^{3} }[/tex]
Zd 4.
a)[tex](6^{9} )^{8} = 6^{9*8} = 6^{72}[/tex]
b)[tex]((-5)^{7})^{3} = (-5)^{21}[/tex]
Zd 5.
[tex]\frac{(b^{6)^{6} * b } }{(b^{5})^{5} } = \frac{b^{37} }{b^{25} }= b^{12}[/tex]
Szczegółowe wyjaśnienie:
Mam nadzieję, że pomogłm(: